Confirmation of intestinal and bladder perforations in a peritoneal dialysis patient using SPECT/CT: a case report and review of literature - Zhang, Xinchao; Hu, Yujing; Jing, Fenglian; Tian, Congna; Wei, Qiang; Li, Kang; Zheng, Lu; Liu, Jiale; Zhang, Jingjie; Bian, Yanzhu (Frontiers in Medicine, 2024)
Background Peritoneal dialysis (PD) is a common treatment method for patients with renal failure. While peritonitis and tube floating migration are commonly observed complications, visceral perforation caused by PD is relatively rare. We present a case report of a patient undergoing PD due to renal failure, who encountered two instances of visceral perforation. In both occurrences, Single-Photon Emission Computed Tomography/Computed Tomography (SPECT/CT) played a pivotal role in providing accurate diagnoses and precise localization of the perforation sites. This report underscores the paramount significance of SPECT/CT in diagnosing visceral perforations in the context of PD. Case presentation A 73-year-old elderly male has been undergoing PD for 1 year due to renal failure. Recently, there has been impaired drainage of the PD catheter. The clinical team suspected the occurrence of peritonitis. The patient underwent a 99mTc Sodium Pertechnetate (99mTc-NaTcO4) SPECT/CT examination, which identified intestinal perforation. After 20 days of conservative treatment, a SPECT/CT follow-up examination revealed the resolution of the intestinal perforation, but a new bladder perforation emerged. The dialysis catheter was methodically and gradually withdrawn in stages while simultaneously performing bladder decompression. Following these interventions, the patient remained free from peritonitis and cystitis. Conclusion The utilization of SPECT/CT proved to be highly valuable in the accurate diagnosis of visceral perforation, a relatively rare complication observed in PD patients.